Application of Criminal Sanction Policy Against Crime Perpetrators of Domestic Violence - Danu Anindhito Kuncoro Putro; Ira Alia Maerani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The research titled: Application of Criminal Sanction Policy Against Crime Perpetrators of Domestic Violence, Problems of this research are: 1) How the policy formulation of the crime of domestic violence? 2) How can the application of criminal sanctions against perpetrators of criminal acts of violence in the home? 3) Constraints are faced judges in the application of criminal sanctions against perpetrators of the crime of domestic violence and efforts to overcome it? The method used in this research using normative research is descriptive qualitative analysis. This study is a literature. The results of the study using sociological juridical concluded that: 1) Policy formulatif against the crime of domestic violence set out in Chapter VIII of Act No. 23 of 2994 Article 44 of physical violence, Article 45 of the violence phisikis, Articles 46, 47, 48 on sexual violence and Article 49 of Neglection. 2). The application of criminal sanctions against perpetrators of criminal acts of domestic violence committed by the judge after going through the process of proving to the charges the prosecutor. Starting from proven facts deeds of witnesses, then the fact juridical considerations and ease further aggravating the new verdict. 3) Constraints faced by judges in the application of criminal sanctions against perpetrators of criminal acts of domestic violence are: a. ) The absence of witnesses cause hearing be postponed, so that the proceedings so that the proceedings be longer than scheduled. b.) The absence attorneys also cause hearing was postponed from the trial process has gone backwards longer than scheduled. c.) The absence of a post mortem result in the judge adjourned the hearing, to include post mortem beforehand. d.) The judge is hard to prove because there were no witnesses who saw directly, and also sometimes victims of domestic violence and perpetrators still love each other, so that judges convict when the weight will result in divorce. e) The absence attorneys also cause hearing was postponed from the trial process has gone backwards longer than scheduled. f.) The absence of a post mortem result in the judge adjourned the hearing, to include post mortem beforehand. g.) The judge is hard to prove because there were no witnesses who saw directly, and also sometimes victims of domestic violence and perpetrators still love each other, so that judges convict when the weight will result in divorce. The absence attorneys also cause hearing was postponed from the trial process has gone backwards longer than scheduled. h.) The absence of a post mortem result in the judge adjourned the hearing, to include post mortem beforehand. i.) The judge is hard to prove because there were no witnesses who saw directly, and also sometimes victims of domestic violence and perpetrators still love each other, so that judges convict when the weight will result in divorce.Keywords: Legal Policy; Crime; Domestic Violence.